Cele i zasady funkcjonowania Wspólnoty Niepodległych Państw - Michur-Ziemba, Maria (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
The agreement on the foundation of the Commonwealth of Independent States (CIS) and other documents signed by the members states to determine the scope of collaboration, their common objectives and principles, were an exclusive legal foundation of CIS until the CIS Statute was signed. The Statute does not determine the range of CIS’s competence and it only stipulates the scope of joint operations of member states. CIS institutions, composed of high ranking officials from member states, only have coordinating competence. However, they are a forum for making common decisions concerning CIS functioning. CIS coordinating organs do not have the authority over member states either, and they can only make recommendations. The Commonwealth of Independent States is relatively young in comparison to other international structures. It is extremely difficult and usually time-consuming to create any form of integration, especially in the realm of politics. It is particularly complicated with respect to CIS as a coherent attitude of all, highly diversified, members is required to work out permanent principles of functioning.